Accreditation and its Role in Indian Context - Bhat, I. K. (Journal of Engineering Education Transformations, 2000)
The formal technical education in India dates back about a century and since then there has been a continuous growth in the number of such institutions. After independence, several technical educational institutions came into existence initially at government initiative and subsequently under selffinancing category.